The Role of Women in Da'wah (Case Study of the Muslimatan NU Branch, Jaddung Pragaan Village) - Ratna Sari binti Sukardin; Ahmad Zukfikar Ali (Values: Jurnal Kajian Islam Multidisiplin, 2025)
This study discusses the role of women in preaching in the organization "Banting Muslimatan Nahdlatul Ulama (NU) in Jaddung Village" in empowering Muslim women through religious, educational and social activities. Muslimatan NU Jaddung Village has an important role as a forum for women with the aim of increasing religious knowledge, life skills and strengthening social solidarity in society. This study uses a qualitative approach with a method (case study) namely through interviews, observation and documentation. The purpose of this study is to analyze the role of women in preaching in "Banting Muslimatan NU Jaddung Pragaan Village" and how the preaching strategy is in the Banting Muslimatan NU Jaddung Pragaan Village and the supporting and inhibiting factors in women's preaching in the Banting Muslimatan NU Jaddung Pragaan Village. The results of the study show that Muslimatan NU in Jaddung Village is not only a means of spiritual development but also contributes to strengthening the role of women in the family and society. In addition, the existence of Muslimatan NU also functions as a driving force in preserving moderate Islamic values ​​amidst dynamic social changes. This study has a significant role in da'wah, both in terms of spiritual, social and economic development. They are able to combine religious values ​​with the needs of the local community and contribute greatly to the process of social change in the village.